Colonial Issues in the Work of George Orwell - Straková, Radka (Univerzita Pardubice, 2011)
This bachelor paper is concerned with the early works of the British author George Orwell which are closely related to the British colonial expansion. The first part of the thesis deals with the terms colonialism and imperialism, and then it focuses on Orwell's direct experience with the British Empire. Further, the analysed works are briefly introduced. The main part of the paper, the detailed analysis of the texts, is divided into two main subchapters. In the first part of the analysis, the works are examined in terms of their depiction of relations of superiority and inferiority between members of the ruling nation and the indigenous population. The second subchapter is then devoted to their portrayal of negative impact of the colonial regime on individuals, who are involved in it.
Kolonialismus v díle George Orwella
Keywords: Britské impérium; Orwell, George; kolonialismus; imperialismus; nadřazenost; osamělost; koloniální systém; loneliness; colonialism; imperialism; superiority; British Empire; colonial system